TINGKAT KEPATUHAN WAJIB PAJAK DAN FAKTOR YANG MEMPENGARUHINYA - Ryandi, Oscar; Kusmana, Endang; Arianto, Arianto (Universitas Muhammadiyah Palembang, 2020)
This research aims to determine the-effect of the application of e-Filing, Corruption Perception, Environment, and Taxation Sanctions the partial or together for submissive taxpayer Pontianak. This research take population of people own tax who registered at the West Pontianak Tax Office (KPP) and East Pontianak KPP. The number of samples taken 100 taxpayers. Data collection techniques use purposive sampling. Data analysis techniques used classic assumption test and multiple regression analysis.The results showed that the application of E-Filing is not positive and significant effect of taxation against Taxpayer Compliance. Corruption Perceptions a positive and significant effect against a compliance by tax payers. Environment a positive and significant effect against a Compliance Taxpayer. Tax Sanctions a positive and significant effect against a Compliance Taxpayer. General simultaneous testing of Application of the e-Filing, Perception of Corruption, Environment, and Tax Sanctions have a positive and significant effect on Taxpayer Compliance.